Education of Msmes in the Order of Improving Product Sales by Using Digital Media in the Middle of the Covid-19 Pandemic - Iswanto Suwarno; Robbi Rahim; Mohammad Aljanabi; Muhammad Ahmad Baballe; Omar Tanane; Irfan Ahmad; Erwin L. Rimban (Peneliti Teknologi Teknik Indonesia, 2021)
The ongoing COVID-19 pandemic throughout the world has had a tremendous impact on people's lives. Not only the health sector, but the economic sector is also paralyzed due to the Covid-19 pandemic, one of the affected countries is Indonesia. This pandemic has greatly affected the economic activities of the community. As a result, many types of businesses experience losses, as happened to MSMEs in the city of Cilegon. During this pandemic, technology has an important role, people prefer to buy everything they need through their smartphones. In the end, it was MSMEs that had utilized technology that were able to survive. The potential of using technology for MSME business development is very influential. Therefore, the role of technology at this time is very large, so the main focus is developing the business of MSME partners to be online-based by utilizing social media, websites and existing market places and developing the potential of each MSME partner who has been assisted.